CUSTOMER EXPERIENCE MANAGEMENT IN BANKING SECTOR - A BRIEF REVIEW - Suvarchala; Rao, V. Narasimha (International Journal of Research -GRANTHAALAYAH, 2018)
The competition among the organizations in financial services sector is continuously increasing. Banking industry is a backbone of nation’s economy and it is one of the largest industries in India in terms of revenue and employment. The banking structure played a major role in the mobilisation of savings and promoting economic development. The intensity of customer-organisation relationship has changed dramatically over time. Customer experience is the product of an interaction between an organisation and a customer over the duration of their relationship. The key elements like strategy, culture, processes and systems etc. impact the CEM in banks. The antecedents like customer knowledge management, satisfaction, trust and loyalty influence the CEM in organizations. This paper is an attempt to trace out the elements of CEM and the various factors leading to the neglect of CEM in banking sector.